(untitled) (International Journal of Language, Literacy and Translation, 2025)
This study sought to ascertain the preferred corrective feedback of ESL students and practiced corrective feedback of their teachers and to determine whether there were any matches or mismatches between preferences of ESL secondary school students and the practices of their ESL teachers for corrective feedback. The study used a quantitative research design. 200 ESL students enrolled in private secondary schools in Karachi, Sindh, Pakistan were given the adopted questionnaire by Ganapathy et al. (2020), which contained forty-four closed-ended items with a range of "strongly agree" to "strongly disagree." In SPSS (version, 22), both descriptive statistics and t-tests were used to analyze the study's two research questions. According to the findings of the first research question, comprehensive corrective feedback was most frequently given by ESL school teachers to their students followed by focused corrective feedback as the second most preferred and practiced corrective feedback. The results of the second research question showed no significant difference between preferred and practiced corrective feedback. The results of this study have important implications for ESL students and teachers. They are also pertinent to language teaching in terms of using corrective feedback in writing class.